Linear and nonlinear optical properties of a quadrupolar carbo-benzene and its benzenic parent: The carbo-merization effect. (April 2021) - Barba-Barba, Rodrigo M.; Chammam, Marwa; Ramos-Ortiz, Gabriel; Listunov, Dymytrii; Velusamy, Jayaramakrishnan; Rodriguez, Mario; Carriles, Ramon; Silva, Carlos; Duhayon, Carine; Kauffmann, Brice; Maraval, Valérie; Chauvin, Remi
Abstract: Herein, the optical properties of thiophene-functionalized quadrupolar carbo -benzenes and a benzenic parent, of generic structure Th–CC–[core]–CC–Th, Th = R2 C4 HS, are comparatively investigated. Beyond the previously unknown dioctylthienylethynylbenzene (core = p -C6 H4, R = n Oct), two bis-dialkylthienylethynyl- carbo -benzenes (core = C18 Ph4, R = n Oct, n Bu) are envisaged for the unique " carbo -aromatic" character of the C18 macrocycle. The three targets were synthesized from the corresponding ethynylthiophenes in 47, 20 and 10% yield, respectively, then characterized by classical methods such as NMR spectroscopy, and X-ray crystallography for one of the carbo -benzenes. Regarding linear and nonlinear optical properties, our results show that the carbo -merization induces a significant shift to lower energies of the one-photon electronic excitations accompanied by an 8-fold increase of the molar extinction coefficient compared to the parent molecule. Intriguingly, these excitations lead to a broad band of photoluminescence comprising decay transitions of the type S 1 → S 0 but also of the type S 2 → S 0 . This phenomenon of emission from higher excited states, which is contrary to Kasha's rule, is assigned to - or revealed by - a reduction of the internal conversion efficiency between S 2 and S 1 . Two-photon induced transitions are also enhanced, the two-photon absorption cross-section ( σ 2PA ) being in average five times larger for the carbo -benzenes than for their benzene parent in the wavelength range 650–950 nm, with a maximum of σ 2PA = 1430 GM (1 GM = 10 −50 cm 4 s/photon). Beyond a moderate nonlinearity, this comparative study provides quantitative insights about the way carbo -merization or insertion of a π-conjugated macrocycle between chromophoric functions (here thiophene rings) can tune optical properties of organic molecules. The optical properties of the bis-dialkylthienylethynyl- carbo -benzenes are also discussed in regard of recent reports on organic chromophores based on other types of π-conjugated macrocyclic cores. Graphical abstract: Image 1 Highlights: A full core-carbo-meric effect analysis on optical properties is reported for the first time. Enhancement of 2 PA in a carbo -benzene is demonstrated versus its benzenic parent. Anomalous luminescence is observed in the carbo- benzene due to simultaneous radiative decays from different excited states. Janus aromatic softness in a "super-soft" chromophore: atom-governed in thiophene (S), size-governed in carbo-benzene (C18).